PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN METODE RELAKSASI UNTUK MENINGKATKAN SELF CONTROL PENGGUNAAN MEDIA SOSIAL PESERTA DIDIK - Ani Nur Rahayu; Anni Suprapti; Rita Sinthia (UNIVERSITAS BENGKULU, 2025)
Abstract This study aims to analyze the effect of group guidance services with relaxation methods on improving self-control of social media use of students at SMK N 3 Bengkulu City. The method used is an experiment with a pre-test and post-test design, involving 32 class X Culinary students who were divided into two groups: experimental and control. The instrument used was a self-control questionnaire, and the data analysis technique used a t-test to compare the results between the two groups. The results showed that there was a significant increase in self-control of social media use in the experimental group, with an average score increasing from 93.7 to 132.9, while the control group only increased from 94.7 to 102. The conclusion of this study is that group guidance services with relaxation methods are effective in improving self-control of social media use of students. Keywords: group guidance, relaxation method, self-control, social media